IMPLEMENTATION OF CHEMICAL CASTRATION PUNISHMENT FOR SEXUAL VIOLENCE AGAINST CHILDREN PERPETRATOR - Imam Sujono (Universitas Internasional Batam, 2022)
The purpose of this research is to perform a legal evaluation of the implementation of Government Regulation No. 70 of 2020 on chemical castration punishment for offenders of sexual assault against children. The normative juridical technique was employed in the creation of this publication, which is a study centered on evaluating the rules or norms found in positive law. According to the research findings, the implementation of this regulation is intended to provide justice for victims, suppress the growth rate of cases, and provide a deterrent effect for perpetrators; these reasons are associated with criminal law theories such as retributive theory, deterrence theory, rehabilitation theory, and resocialization theory. Human Rights Law considers this penalty to be a breach of human rights, as outlined in the Universal Declaration of Human Rights and Human Rights Law No. 39 of 1999. Denmark, Sweden, Finland, Norway, Poland, the US state of California, Australia, New Zealand, Russia, South Korea, Israel, Estonia, and Moldova are some of the countries that have implemented this penalty. Countries that have implemented this penalty have two basic goals: first, to apply this punishment as a national punishment, and second, to apply this punishment voluntarily from the perpetrator.